HEALTH KNOWLEDGE AND INTERDISCIPLINARITY IN PALLIATIVE CARE - da Conceição Sampaio Lóss, Juliana; Evangelista Dias, Vinícius; Lacerda Tinoco Boechat Cabral, Hildeliza; Henrique Medeiros de Souza, Carlos (LINKSCIENCEPLACE, 2026)
Palliative care can be considered a necessary and salutary aspect for terminally ill patients, with chronic diseases or difficult diseases, with a poor prognosis in which death is imminent, where the greater goal of care is in relieving pain and coping the suffering. The present study emerges from the emergence of treating patients in palliative care in an interdisciplinary way, in which all the hopes and fields of knowledge and health combine their theory and praxis, in order to fulfill ideal palliative care, with the ultimate goal of to provide dedication that aims at the integrality of the subject and his family, besides subsidizing a dialogue between health knowledge and interdisciplinary. Faced with the increase of diseases beyond the possibility of cure and its various ways of dealing with such demand, the following problem arises: How the areas of health knowledge in palliative care work, their performance is individualistic or interdisciplinary. It is justified, given the existing demand of patients and families who need Palliative Care, as well as the urgency to discuss the interdisciplinary with the involved actors, health professionals. The aim of this study is to understand the articulated performance of the health professionals that make up the interdisciplinary team of global patient care (Pharmacy, medicine, nursing, psychology, occupational therapy, dentistry) regarding the effectiveness of palliative care. This is qualitative field research. A semi-structured interview was used, with questions about the health professional's action in relation to palliative care and their interdisciplinary action. The professionals were voluntarily selected, completing a sample of 8 individuals from the different health areas. All collected material was transcribed in its entirety and analyzed through Bardin's content analysis.